The role of diseases in unifying the health of global estuaries - Tallam, Krti; White, Elliott (Frontiers in Marine Science, 2023)
Establishing a universal indicator of estuary health is an ongoing challenge for coastal ecology that is made more pressing due to the threat that climate change and anthropogenic activity pose to them. Historically, estuarine health was measured through basic physical, chemical, and biological traits, which have been used to routinely monitor estuaries for more than 30 years. However, it is unclear if they are dynamic enough to accurately assess ecosystem health changes driven by the pressures of climate change and anthropogenic activity. Measuring estuarine health indicators and noting incipient indicators relevant to the evolving threats of climate- and anthropogenic-related stressors on estuarine ecosystems is vital for safeguarding them into the future. Monitoring the presence and vitality of disease in estuarine ecosystems may prove to be a significant indicator of estuarine health. Here we review 22 years of literature (354 papers) to identify the role of marine diseases as critical indicators of long-term estuary health compared to traditional methods, with the goal of identifying a key indicator and underlying unifier of other health metrics. As indicators of both general ecosystem health and of multiple other stressors, diseases play a disproportionately significant role in estuary health in the face of climate- and anthropogenic-related stressors. Marine diseases are a unifier of structural and functional estuary health indicators and must be observed and modeled further.